2022
DOI: 10.1038/s41598-022-20792-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal dynamics of phytoplankton community in a well-mixed temperate estuary (Sado Estuary, Portugal)

Abstract: Estuaries are highly productive ecosystems, which are strongly affected by several anthropogenic pressures. Phytoplankton is a key element for assessing the ecological quality status in these transitional waters. Moreover, understanding physico-chemical and biological drivers is crucial to disentangle their effect on the structure of phytoplankton community. The present work aims to study the effect of the main physico-chemical drivers on the phytoplankton community structure and dynamics in a temperate well-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…Research conducted by Witariningsih, et al (2020), in the waters of the Lombok Strait also found the most species from the Bacillariophyceae class. This is also supported by Santos, et al (2022) which state that many types of phytoplankton found in the Estuary Area in Sado, Portugal come from the Bacillariophyceae class. The least phytoplankton found at the study site came from the Pyramimonadophyceae class (2%) with only 1 genus, namely Halosphaera and from the Dinophyceae class (2%) also only found 1 genus, namely Peridinium.…”
Section: Resultssupporting
confidence: 64%
“…Research conducted by Witariningsih, et al (2020), in the waters of the Lombok Strait also found the most species from the Bacillariophyceae class. This is also supported by Santos, et al (2022) which state that many types of phytoplankton found in the Estuary Area in Sado, Portugal come from the Bacillariophyceae class. The least phytoplankton found at the study site came from the Pyramimonadophyceae class (2%) with only 1 genus, namely Halosphaera and from the Dinophyceae class (2%) also only found 1 genus, namely Peridinium.…”
Section: Resultssupporting
confidence: 64%
“…Climate change affects the primary production, that is, phytoplankton, in the aquatic environment (Behrenfeld et al, 2006;Doney, 2006;Doney et al, 2012). It has been confirmed that the phytoplankton was climate-driven, either in basin scale or on a more small scale, like bays, estuaries (Santos et al, 2021(Santos et al, , 2022. Nevertheless, much less knowledge is known about the marine scale due to the complex influences, and lack of long-term observations.…”
Section: Teleconnection Between the Coastal Phytoplankton Blooms And ...mentioning
confidence: 99%
“…Marine phytoplankton are naturally believed and already proven to be influenced by climate oscillations. For instance, although strong correlations between marine phytoplankton and modes of climate variability (i.e., North Atlantic Oscillation, El Ni ño-Southern Oscillation) were reported for several lakes in coastal areas, much less is known for large scales in the marine as a unit, comparing to small and medium scales (i.e., bays, estuaries) (Santos et al, 2021(Santos et al, , 2022. Furthermore, on large level, the ultimate drivers of climate oscillations on phytoplankton are not yet understood, and the consequences of the ecosystem remain uncertain (Menge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the low-inflow (average river inflow 1-60 m 3 s À1 ) Sado Estuary system in Portugal is also typically dominated by diatoms, although an increasing abundance of cryptophytes in the upper estuary was observed over the past 20 yr, potentially due to nutrient enrichment patterns (Santos et al 2022). Cryptophytes were the third most abundant taxa in the Mission-Aransas Estuary, and although no change was detected across the drought-to-wet transition, the relative abundance of cryptophytes was associated with high DIN and PO 4 3À concentrations (Fig.…”
Section: Phytoplankton Biomass Increased During Wet Conditionsmentioning
confidence: 99%